2017
DOI: 10.3390/ijms18020357
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Two Insulin Receptor Genes Disrupts Nymph-Adult Transition of Alate Brown Citrus Aphid

Abstract: Insulin receptors play key roles in growth, development, and polymorphism in insects. Here, we report two insulin receptor genes (AcInR1 and AcInR2) from the brown citrus aphid, Aphis (Toxoptera) citricidus. Transcriptional analyses showed that AcInR1 increased during the nymph–adult transition in alate aphids, while AcInR2 had the highest expression level in second instar nymphs. AcInR1 is important in aphid development from fourth instar nymphs to adults as verified by dsRNA feeding mediated RNAi. The silenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 49 publications
1
40
0
9
Order By: Relevance
“…Because of its effects on the expression of these genes, the IIS pathway is thought of as a phenotypic plasticity pathway, generating bodies that match their environment with respect to size, shape and physiology. Correspondingly, multiple studies have implicated the IIS pathway in the regulation of a wide variety of plasticities (Emlen, Warren, Johns, Dworkin, & Lavine, ; Snell‐Rood & Moczek, ; Tang et al, ; Wheeler, Buck, & Evans, ; Wolschin et al, ; reviewed in Nijhout and McKenna, 2018), including late nymphal stage differences between winged and wingless morphs of two aphid species (Ding et al, ; Guo, Zhang, & Liu, ), and long and short‐winged morphs of the brown planthopper, Nilaparvata lugens (Xu et al, ) and the soapberry bug, Jadera haematoloma (Fawcett et al, ). Interestingly, the latter two studies showed different functional requirements for the two insulin receptors, the paralogs InR1 and InR2.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its effects on the expression of these genes, the IIS pathway is thought of as a phenotypic plasticity pathway, generating bodies that match their environment with respect to size, shape and physiology. Correspondingly, multiple studies have implicated the IIS pathway in the regulation of a wide variety of plasticities (Emlen, Warren, Johns, Dworkin, & Lavine, ; Snell‐Rood & Moczek, ; Tang et al, ; Wheeler, Buck, & Evans, ; Wolschin et al, ; reviewed in Nijhout and McKenna, 2018), including late nymphal stage differences between winged and wingless morphs of two aphid species (Ding et al, ; Guo, Zhang, & Liu, ), and long and short‐winged morphs of the brown planthopper, Nilaparvata lugens (Xu et al, ) and the soapberry bug, Jadera haematoloma (Fawcett et al, ). Interestingly, the latter two studies showed different functional requirements for the two insulin receptors, the paralogs InR1 and InR2.…”
Section: Discussionmentioning
confidence: 99%
“…We also explored the functions of AcVg and AcVgR in an RNAi bioassay using plant-stem-mediated dsRNA feeding, which has been used previously to silence genes encoding chitin synthase and insulin receptors in Aph. citricidus (Shang et al, 2016b;Ding et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome sequencing is an efficient and low-cost method by which to explore gene expression patterns at multiple developmental stages 6,7 , tissues in insects 8,9 . Many insect transcriptomes have been obtained using next-generation sequencing techniques for functional genomic studies 10,11 . For example, in Ceratitis capitata, a conserved Maleness-on-the-Y gene was isolated to be involved in the male sex determination by RNA-Seq.…”
Section: Background and Summarymentioning
confidence: 99%